1993
DOI: 10.1111/j.1440-1681.1993.tb01664.x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Norepinephrine Content in the Medulla Oblongata in Severely Hypertensive Rats

Abstract: 1. To clarify possible abnormalities in catecholamines in the medulla oblongata in relation to severe hypertension, the authors measured changes in catecholamine levels in the medulla oblongata of malignant stroke-prone spontaneously hypertensive rats (M-SHRSP). Effects of the adrenal medullae and peripheral nerves were ruled out by adrenal demedullation and chemical sympathectomy. 2. The level of norepinephrine in the medulla oblongata was significantly lower in untreated M-SHRSP than in untreated WKY (contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
(16 reference statements)
0
6
0
1
Order By: Relevance
“…Takami and co‐workers found that in young, mature (10 weeks) severely hypertensive stroke‐prone SHR, the tissue level of NA in the medulla oblongata was significantly lower than in the control strain WKY rat (Takami et al 1993). Similar observations were reported by others and, interestingly, the medulla oblongata was the only brain region where a decrease in NA in the SHR was significant (S143).…”
mentioning
confidence: 99%
“…Takami and co‐workers found that in young, mature (10 weeks) severely hypertensive stroke‐prone SHR, the tissue level of NA in the medulla oblongata was significantly lower than in the control strain WKY rat (Takami et al 1993). Similar observations were reported by others and, interestingly, the medulla oblongata was the only brain region where a decrease in NA in the SHR was significant (S143).…”
mentioning
confidence: 99%
“…These results suggested "…that lower Dbh in the young SHR presents a 'bottleneck' in catecholamine biosynthesis, leading to dopamine accumulation and catecholamine depletion in adrenergic cells, which then contributes to the pathogenesis of hypertension" (Jirout et al 2010). It has been suggested that reduced DBH activity in the brain leads to higher dopamine and lower norepinephrine levels which might represent a possible mechanism connecting reduced central DBH activity with increased blood pressure (Howes et al 1984, Cornish et al 1997, Takami et al 1993. However, in our previous studies, we did not determine Dbh expression levels or catecholamine levels in the brainstem (Jirout et al 2010).…”
Section: Introductionmentioning
confidence: 65%
“…1C), likely leading to impaired or reduced ability of SHR to store catecholamines in this brain region vital to BP regulation. In fact, it was previously shown that the norepinephrine content was decreased in the NTS (in the medulla oblongata of the brainstem) of SHR versus WKY (28), and in the medulla oblongata (brainstem) of SHRSP versus WKY (29).…”
Section: Central Versus Peripheral Expression Of Chromogranin Amentioning
confidence: 94%
“…We are not the first to hypothesize involvement of the brainstem in the pathogenesis of hypertension in the SHR. Takami et al (29) hypothesized that since norepinephrine was decreased in the NTS in the medulla oblongata of SHR, and since norepinephrine has an inhibitory effect in the NTS on systemic BP elevation, 'the suppression of negative feedback due to a decrease in the activity of inhibitory neurons in the medulla oblongata appears to be involved in the development and progression' of hypertension in the SHR (29); we build upon the conclusions of Takami et al (29) to include a genetic basis at the Chga locus.…”
Section: Chga As a Contributor To The Pathogenesis Of Hypertension Inmentioning
confidence: 99%